Constructing and storytelling: accommodating different play orientations in learning spatial thinking - Sonneveld, Leonie; Klapwijk, Remke M.; Stappers, Pieter Jan (Frontiers in Education, 2024)
Spatial ability is malleable and belongs in the preschool. For preschoolers, many analytical activities with one correct answer have been developed. Less is known about employing open ended design assignments to creatively practice spatial thinking. Little attention has been paid to the mutual qualitative differences between children when engaged in spatial thinking and insight in children's motivation is lacking. As design and play have much in common, our first study investigated play orientations during free play of 49 Dutch preschoolers during free play in a low and a high SES school. Participative interviews and observations in the construction and home corners of two schools uncovered different play orientations-construction and pretend play -and either a focus on open-ended objects or on defined objects. In a subsequent study, the influence of these play and object orientations on how children design was investigated. This study with 13 children also used generative design research methods grounded in ethnographic research and therapeutic practices. Using an empathic, story-based, open-ended design challenge, results showed that play-orientations of children influence the length and nature of the design activities as well as the design outcomes. Children with a pretend-play orientation are longer engaged and talk more about the character involved. They usually built organic structures with a variety of objects, while construction-oriented children mainly built sturdy and geometrical structures and mainly used open-ended objects. In all play orientations, spatial thinking was practiced and children were spatially challenged. For example, in all orientations difficulties arose around getting the character in out the structure, however, as different structures were build, the nature of these difficulties were also different. Open-ended design activities that contain characters and problems children can empathize with are a valuable addition to the palette of activities to develop spatial thinking in early classrooms. Our study shows that design activities stimulate children to practice spatial thinking in a creative context and have the ability to engage children with a pretend-play orientation who are otherwise less engaged in construction. The play-orientations and object-orientations are informative for research and the development of spatial educational interventions aiming at a diversity of learners.